Significance of counselling orientation on supervision outcomes among trainee counsellors: comparison between previous and current study in Malaysia - Ghazali, N. M.; Hii, H. N.; Wan Jaafar, W. M.; Anuar, A.; Aden, E.; Yahyah, F. (2020)
The purpose of this study was to compare the finding of counselling orientation on supervision outcomes (satisfaction, performance and competency) among trainee counsellors on the previous and current study. The research design of this study was quantitative in nature, using survey research. The counselling orientation was measured the theoretical background between trainee counsellors and their supervisor. The counselling orientation, which measured using Selective Theory Sorter-Revised (STS-R), the satisfaction and performance were measured by Supervision Outcomes Survey and the competency measured by Counseling Competencies Scale (CCS). The sample size for previous study was 120 respondents and the current study was 76 trainee counsellors. The respondents were selected using the proportionate stratified random sampling technique. The test analyses used were one-way analysis of variance (ANOVA) and independent samples T-test. From the result for congruence of counselling orientation was t (74) =0.46; p=0.65 (two-tailed), p>0.05. Thus, the overall results showed that the counselling orientation had no significant effect to the level of competence of counselor trainee (p< 0.05), aligned with Conscious Competence Learning Theory and Model of Dynamic Process for Supervisee Learning, where truly responsive supervision can boost supervisee learning. Insignificance of factors (frequency and theoretical orientation), with p> 0.05, contradicted with System Approach in Supervision Model (SAS) due to the difference in environmental context (Nor Mazlina Ghazali, 2015). Future work will be needed in assessing more factors in supervisory process for similar studies to be carried out. In addition, the location of the study can be varied to carry out the study using a more diverse population. Moreover, future researchers are encouraged to use a larger number of samples and expanding the subvariables of the dependent variable and mixed method of data collection method by adding qualitative method of interview for additional information in the study.